Visual perspective and the characteristics of mind wandering - Christian, Brittany M.; Miles, Lynden K.; Parkinson, Carolyn; Macrae, C. Neil (Frontiers in Psychology, 2013)
When the mind wanders away from the here-and-now toward imaginary events, it typically does so from one of two visual vantage points ― a first-person perspective (i.e., the world is seen as it is in everyday life) or a third-person perspective (i.e., the world is seen from the viewpoint of an outside observer). While extant evidence has detailed consequences that ensue from the utilization of these distinct points of view, less is known about their more basic properties. Here, we investigated the prevalence, demographics and qualities associated with the visual perspective that people spontaneously adopt when the mind wanders. The results from a cross-cultural survey (N = 400) revealed that almost half of the participants (46%) typically utilize a third-person perspective when mind wandering. Further, culture and gender were shown to impact the distribution of first- and third-person imagers. Specifically, a first-person perspective was more common among participants from Western nations and females, while participants from Eastern cultures resonated more strongly with a third-person perspective. Moreover, these factors were also shown to impact qualities (e.g., temporal locus, vividness) of mental imagery. Taken together, the current findings elucidate the prevalence of first- and third-person visual perspectives and detail individual differences that influence the qualia of mind wandering.